A single-atom copper catalyst and its preparation method and its application in efficient disinfection with activated O2.

CN122999249APending Publication Date: 2026-10-30TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610983922.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,在真实电化学工作条件下,单原子位点会发生动态结构重构,其真正的活性位点与反应机理尚不明确

Benefits of technology

1、本发明首次将单原子铜催化剂(SA-CuN4/NC)应用于电化学水消毒领域,并揭示了其在阴极电位驱动下发生自重构(从CuN4单原子位点转变为Cu2-CuN2团簇)是高效、选择性生成·OH的关键。这一发现为设计高性能环境电催化材料提供了新的理论依据。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999249A_ABST
    Figure CN122999249A_ABST
Patent Text Reader

Abstract

The application provides a single-atom copper catalyst and a preparation method and application thereof in efficient disinfection by activating O2, and belongs to the technical field of water treatment and disinfection. The single-atom copper cathode electrode is constructed by a slow-release pyrolysis strategy, has high electrochemical activity and a large specific surface area, and can provide abundant reaction active sites. On the surface of the electrode, not only can Cu2-CuN2 clusters be formed by self-reconstruction of CuN4 coordination structures under the driving of a cathode potential to realize a three-electron oxygen reduction path and selectively generate controllable concentration of hydroxyl radicals, but also the generation concentration of the hydroxyl radicals can be accurately controlled by adjusting the metal content, so that the bacterial aggregation effect caused by excessive hydroxyl radicals is avoided, the continuous penetration and damage of the hydroxyl radicals to the cell membrane of dispersed-state antibiotic-resistant bacteria cells are strengthened, the inactivation efficiency of ARB is improved, the release and degradation of intracellular antibiotic-resistant genes are accelerated, and the ultrafast inactivation of ARB and the complete removal of ARGs are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment and disinfection technology, and in particular to a single-atom copper catalyst, its preparation method, and its application in highly efficient disinfection using activated O2. Specifically, it is an electrochemical method that achieves controllable hydroxyl radical generation by precisely regulating the self-reconfiguration of single-atom copper sites, thereby simultaneously and efficiently inactivating antibiotic-resistant bacteria (ARBs) and removing antibiotic resistance genes (ARGs). Background Technology

[0002] Antibiotic-resistant bacteria (ARBs) and antibiotic resistance genes (ARGs) pose a serious threat to public health and ecological security as emerging environmental pollutants. Traditional biological treatment processes are insufficient for their complete removal, while conventional disinfection technologies such as ultraviolet light, chlorination, and ozonation, although effective in inactivating pathogens, have limitations including high reagent consumption, the generation of toxic byproducts, and difficulty in effectively destroying intracellular / extracellular ARGs. Therefore, there is an urgent need to develop a green, efficient, and integrated treatment technology that can simultaneously remove ARBs and ARGs.

[0003] In recent years, electrochemical oxidation technology has attracted widespread attention due to its sustainability and ease of operation. In-situ generation of reactive oxygen species (ROS) via the cathode oxygen reduction reaction (ORR) is an effective way to achieve green disinfection. Among them, hydroxyl radicals (·OH) have the highest oxidizing power (2.8 V vs. NHE), capable of indiscriminately attacking microorganisms and cellular components. However, how to precisely control the amount of ·OH generated to achieve efficient disinfection while avoiding excessive ·OH that could lead to bacterial aggregation and reduced disinfection efficiency remains a key scientific challenge.

[0004] Single-atom catalysts (SACs) have shown great potential in regulating ORR selectivity due to their highest atom utilization and tunable electronic structure. Theoretically, by precisely designing the coordination environment of the metal center, the ORR pathway can be controlled to selectively generate ·OH. However, under real electrochemical operating conditions, single-atom sites undergo dynamic structural reconstruction, and their true active sites and reaction mechanisms remain unclear. Currently, there are no reports on using single-atom copper catalysts at the cathode via the three-electron oxygen reduction (3e-ORR) pathway and leveraging their potential-driven self-reconstruction properties to precisely control ·OH generation, thereby achieving efficient and controllable water disinfection. Summary of the Invention

[0005] To address the above technical problems, this invention provides a single-atom copper catalyst, its preparation method, and its application in efficient O2 disinfection. This invention utilizes a single-atom copper catalyst (SA-CuN4 / NC) with a CuN4 coordination structure as the cathode. Under cathode potential-driven conditions, self-reconstruction occurs to form Cu2-CuN2 clusters, achieving three-electron oxygen reduction (…). The pathway selectively generates hydroxyl radicals (·OH); at the same time, the concentration of ·OH generation can be precisely controlled by adjusting the metal loading of single-atom copper, thereby achieving ultra-fast inactivation of ARB (8-log removal within 1 minute) and complete removal of ARGs.

[0006] The first objective of this invention is to provide a single-atom copper catalyst, wherein the single-atom copper catalyst uses montmorillonite as a support, and C3N4 containing a CuN4 coordination structure is loaded on the surface of the support. In some embodiments of the present invention, the loading of single-atom copper is 0.5-2.7 wt%, and exemplaryly, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7 wt%, or any range between two values, preferably 0.5-2 wt%, 1.0-2 wt%, 1.0-1.5 wt%, and more preferably 1.5-2 wt%.

[0007] A second objective of this invention is to provide a method for preparing a single-atom copper catalyst, comprising the following steps: Montmorillonite was added to the copper source solution, and the first ultrasonic treatment was performed to remove Cu. 2+ Ion exchange enters the interlayer of montmorillonite, resulting in a mixture; Melamine was added to the resulting mixture, and the mixture was subjected to a second ultrasonic treatment to ensure homogeneity. The mixture was then pyrolyzed under an inert atmosphere to obtain the precursor. The obtained precursor was impregnated in an acid solution, washed and dried to obtain the SA-CuN4 / NC electrode material, namely the single-atom copper catalyst.

[0008] In some embodiments of the present invention, the copper source is selected from one or more of copper nitrate, copper chloride, and copper sulfate.

[0009] In some embodiments of the present invention, the mass ratio of the copper source, montmorillonite, and melamine is (0.239-1.912):2:2; In this invention, melamine undergoes pyrolytic polymerization to form a nitrogen-doped carbon substrate, while the gas generated in situ simultaneously converts Cu... 2+ The copper ions are slowly released from the interlayer of montmorillonite, regulating the coordination structure of the single copper atoms to CuN4. Montmorillonite acts as a spatial confinement agent, achieving the slow release of copper ions through the interlayer confinement effect.

[0010] The duration of the first or second ultrasound treatment is 20-40 minutes.

[0011] In some embodiments of the present invention, the inert gas in the inert atmosphere is selected from nitrogen and / or argon; The pyrolysis temperature is 500-600℃, and the pyrolysis time is 3-4 h; The immersion treatment time is 6-8 hours; the acid solution is 2-5 M H2SO4.

[0012] A third objective of the present invention is to provide a cathode oxygen reduction reaction, comprising a cathode, wherein the cathode comprises the aforementioned single-atom copper catalyst.

[0013] A fourth objective of this invention is to provide the application of the aforementioned cathode oxygen reduction reaction in in situ inactivation of antibiotic-resistant bacteria and removal of antibiotic resistance genes.

[0014] The fifth objective of this invention is to provide the application of the aforementioned cathode oxygen reduction reaction in the efficient disinfection of activated O2.

[0015] In some embodiments of the present invention, the specific methods of the application are as follows: Using a two-electrode or three-electrode system, the single-atom copper catalyst is used as the cathode and a platinum sheet is used as the anode. Electrolysis is carried out in an aqueous solution containing a supporting electrolyte through a constant current or constant potential mode. The hydroxyl radicals generated in situ at the cathode are used to disinfect the target water body.

[0016] Furthermore, the active site of the single-atom copper-carbon based electrode (SA-CuN4 / NC) is a CuN4 coordination structure. During the electrochemical reduction process, the CuN4 sites undergo self-reconfiguration under the action of protons, forming stable Cu2-CuN2 clusters, which serve as the three-electron oxygen reduction (3e... - ORR is the true active site for generating ·OH.

[0017] Furthermore, by adjusting the cathode potential or the catalyst metal loading, the degree of self-reconfiguration of single-atom copper sites can be controlled, thereby precisely regulating the concentration of ·OH generated. The disinfection efficiency is highest when the concentration of ·OH is 11.5 μM; excessively high ·OH concentrations (such as 47.9 μM) will induce bacterial aggregation and reduce disinfection efficiency.

[0018] Furthermore, the supporting electrolyte is sodium sulfate electrolyte with a concentration of 0.05 M; the pH of the electrolyte is 7.

[0019] Furthermore, the antibiotic-resistant bacteria (ARB) in the target water body are tetracycline-resistant Escherichia coli (E. coli) and the tetracycline resistance gene (tetB) they carry.

[0020] In this invention, a slow-release pyrolysis strategy is used to construct a single-atom copper cathode electrode (SA-CuN4 / NC), which exhibits high electrochemical activity and a large specific surface area, providing abundant reactive sites. On the surface of this electrode, the CuN4 coordination structure can undergo self-reconstruction under cathode potential to form Cu2-CuN2 clusters, selectively generating controllable concentrations of hydroxyl radicals (·OH) via the three-electron oxygen reduction (3e-ORR) pathway. Simultaneously, the concentration of ·OH generated can be precisely controlled by adjusting the metal content, avoiding bacterial aggregation caused by excessive ·OH, enhancing the continuous penetration and destruction of the cell membrane of dispersed antibiotic-resistant bacteria (ARBs) by ·OH, improving the inactivation efficiency of ARBs, and thus accelerating the release and degradation of intracellular antibiotic resistance genes (ARGs), thereby achieving ultra-fast inactivation of ARBs (8-log removal within 1 minute) and complete removal of ARGs.

[0021] The technical solution of the present invention has the following advantages compared with the prior art: 1. This invention is the first to apply a single-atom copper catalyst (SA-CuN4 / NC) to the field of electrochemical water disinfection, and reveals that its self-reconfiguration under cathode potential drive (transformation from CuN4 single-atom sites to Cu2-CuN2 clusters) is the key to the efficient and selective generation of ·OH. This discovery provides a new theoretical basis for the design of high-performance environmental electrocatalytic materials.

[0022] 2. This invention maximizes disinfection efficiency by precisely controlling the concentration of ·OH generated. Unlike existing technologies that generally pursue high concentrations of active species, this invention discovers that a moderate concentration of ·OH (11.5 μM) can effectively penetrate and destroy dispersed bacterial cells, achieving ultra-rapid inactivation; while excessive ·OH (47.9 μM) can induce bacterial aggregation and reduce disinfection effectiveness. This concentration-dependent disinfection mechanism has significant guiding implications for practical applications.

[0023] 3. The method provided by this invention can simultaneously and efficiently remove ARBs and intracellular / extracellular ARGs. The strong oxidizing properties of ·OH can destroy the cell membrane structure, release and further degrade ARGs, thereby blocking the spread of antibiotic resistance genes in the environment from the source and overcoming the shortcomings of traditional disinfection technologies in effectively removing ARGs.

[0024] 4. The method of this invention is green and sustainable, using oxygen from the air as an oxidant, eliminating the need for external chemical agents and avoiding the generation of toxic byproducts. Furthermore, this catalyst exhibits good stability and adaptability in complex aquatic matrices (such as those with different pH levels and coexisting anions and cations), showing broad prospects for engineering applications. Attached Figure Description

[0025] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein... Figure 1 The image shows the SEM image of SA-CuN3 / NC obtained in Comparative Example 1.

[0026] Figure 2 The image shows the SEM image of SA-CuN4 / NC obtained in Example 1.

[0027] Figure 3 EXAFS curve fitting plots were performed in R space for SA-CuN3 / NC obtained in Comparative Example 1 and SA-CuN4 / NC obtained in Example 1.

[0028] Figure 4 EPR spectra of the electrochemical SA-CuN3 / NC / O2 and SA-CuN4 / NC / O2 systems using DMPO as a trapping agent.

[0029] Figure 5 EPR spectra of the electrochemical SA-CuN3 / NC / O2 and SA-CuN4 / NC / O2 systems using TEMP as a trapping agent.

[0030] Figure 6 The EPR spectra of SA-CuN4 / NC(O2) systems with different metal contents were obtained at 15 minutes using DMPO as a trapping agent.

[0031] Figure 7 The image shows the Cu K-edge EXAFS spectra of SA-CuN4 / NC materials under in-situ conditions when different potentials (OCP, 0.8, 0.6, 0.4, 0.2 V vs. RHE) are applied.

[0032] Figure 8 A graph showing the relationship between reactive oxygen species generation and large ARB degradation using SA-CuN4 / NC under different potential conditions.

[0033] Figure 9 The graph shows the relative content of intracellular and extracellular ARGs after ARBs were treated with medium and high intensity ·OH. Detailed Implementation

[0034] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0035] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0036] Example 1:

[0037] This embodiment provides a method for preparing the single-atom copper catalyst SA-CuN4 / NC (1.5wt%CuN4 / NC), as detailed below: S1. Weigh 0.956 g Cu(NO3)2·3H2O and dissolve it in 4 mL of deionized water. Add 2 g montmorillonite (MMT) and sonicate for 30 min to allow Cu to dissolve. 2+ Sufficient exchange occurs between the MMT layers to obtain a mixture; S2. Add 2 g of melamine to the above mixture and continue to sonicate for 30 min to mix evenly; S3. Place the mixture in a quartz glass bottle, wrap it with aluminum foil, and pyrolyze it in a muffle furnace at 550°C for 3 hours. S4. The pyrolysis product was immersed in 5 M H2SO4 at 80℃ for 6 h to remove possible copper nanoparticles or oxides. S5. The product was washed successively with deionized water and ethanol, and dried at 60°C for 12 h to finally obtain 1.5wt% SA-CuN4 / NC.

[0038] Example 2

[0039] The examples provide a specific method for preparing 2.7wt% SA-CuN4 / NC with a high metal loading, as detailed below: The preparation process was the same as that of 1.5wt%SA-CuN4 / NC in Example 1, but the amount of copper nitrate added was 1.912g, and finally a high metal loading of 2.7wt%SA-CuN4 / NC was obtained.

[0040] Example 3

[0041] The examples provide a specific preparation method for 0.5wt% SA-CuN4 / NC with a low metal loading, as detailed below: The preparation process was the same as that of 1.5wt%SA-CuN4 / NC in Example 1, but the amount of copper nitrate added was 0.239g, and finally a high metal loading of 0.5wt%SA-CuN4 / NC was obtained.

[0042] Comparative Example 1 This comparative example provides a specific method for preparing the single-atom copper catalyst 1.5wt% CuN3 / NC, as shown below: The preparation process is the same as that of 1.5wt%SA-CuN4 / NC in Example 1, but without the addition of MMT. The mixture of copper nitrate and melamine is directly pyrolyzed to obtain 1.5wt%CuN3 / NC.

[0043] The prepared materials were characterized by scanning electron microscopy (SEM) to determine their surface morphology and structure, as shown below. Figure 1 , Figure 2 As shown: The material after pyrolysis exfoliation in Comparative Example 2 is a porous carbon material with a layered structure and a large specific surface area. Furthermore, no obvious metal particles or nanoclusters were observed on the surface of the 1.5wt% SA-CuN3 / NC and 1.5wt% SA-CuN4 / NC electrode materials, indicating that the 1.5wt% SA-CuN4 / NC and 1.5wt% SA-CuN3 / NC electrode materials were successfully prepared. EXAFS fitting results ( Figure 3 The results indicate that the coordination number of Cu in SA-CuN4 / NC is approximately 3.7, indicating a CuN4 structure; while the coordination number of 1.5wt% SA-CuN3 / NC is approximately 2.5, indicating a CuN3 structure.

[0044] Application Example 1 Using 1.5 wt% SA-CuN4 / NC and 1.5 wt% SA-CuN3 / NC from Example 1 and Comparative Example 1 as electrochemical cathodes, hydroxyl radicals (·OH) were detected using an in-situ electrochemical electron paramagnetic resonance spectrometer (EPR, ELEXSYS-II E 500, Bruker, Germany). A concentration of 0.22 mol / L was used. -1 DMPO, acting as a trapping agent, forms a complex DMPO-·OH with ·OH. An EPR resonance frequency of 9.834 GHz was set, and the peristaltic pump, electrochemical workstation, and EPR spectrometer were controlled via RS485 serial communication to achieve coordination between the electrochemical sequence and the two-dimensional EPR time series.

[0045] Reactive oxygen species (ROS) generated during oxygen reduction reactions in O2-saturated electrolytes using 1.5 wt% SA-CuN4 / NC and 1.5 wt% SA-CuN3 / NC catalysts as cathodes were detected by electron paramagnetic resonance (EPR). Catalyst inks were prepared by ultrasonically dispersing 20 mg each of the 1.5 wt% SA-CuN4 / NC and 1.5 wt% SA-CuN3 / NC catalysts in 2.5 mL of a mixed solvent consisting of deionized water, ethanol, and Nafion solution (volume ratio 1:1.5:0.05) for 30 min. The catalyst inks were then drop-coated onto a 2 × 2 cm² area. 2 The carbon paper electrode surface, after natural drying, serves as the working electrode, with a catalyst loading of approximately 5 mg / cm³. 2A platinum sheet was used as the counter electrode and placed in an O2-saturated 0.05 M Na2SO4 electrolyte. Electrolysis was performed using a constant current mode, with a constant current of 10 mA applied to the working electrode for 1-30 min. During electrolysis, 20 μL of electrolyte was added to a solution containing 20 μL of DMPO (0.22 mol / L). -1 The mixture was thoroughly mixed in a centrifuge tube and then rapidly transferred to a capillary. The capillary was placed in a quartz EPR sample tube and quickly transferred into the resonant cavity of the EPR spectrometer. Spectra were acquired at room temperature. The results are as follows: Figure 4 As shown, using DMPO as a capture agent, a significant ·OH signal was detected in the SA-CuN4 / NC / O2 system, while almost no ·OH was detected in the SA-CuN3 / NC / O2 system. This indicates that SA-CuN4 / NC can selectively catalyze the three-electron oxygen reduction pathway to generate ·OH, while SA-CuN3 / NC does not have this function.

[0046] Further detection of the generated substances in the system using TEMP as a capture agent. 1 O2, the result is as follows Figure 5 As shown. Under energized conditions, no significant [effects] were detected in either the SA-CuN4 / NC system or the SA-CuN3 / NC system. 1 The O2 signal indicates that neither system produces singlet oxygen during oxygen reduction.

[0047] EPR test results indicate that the SA-CuN4 / NC system can selectively generate ·OH by activating O2, mainly via the three-electron oxygen reduction radical pathway; while the SA-CuN3 / NC system hardly generates ·OH and is difficult to directly and efficiently inactivate antibiotic-resistant bacteria.

[0048] Application Example 2: To further investigate the effect of metal loading on the ·OH generation efficiency, this invention, under the same experimental conditions, used 0.5wt% SA-CuN4 / NC, 1.5wt% SA-CuN4 / NC, and 2.7wt% SA-CuN4 / NC (copper contents of 0.5 wt%, 1.5 wt%, and 2.7 wt%, respectively) as cathode materials, and employed the same EPR test method to detect the ·OH generated during electrolysis. The specific operation was as follows: 20 mg of each of the three catalysts was weighed and dispersed in 2.5 mL of a mixed solvent composed of deionized water, ethanol, and Nafion solution (volume ratio 1:1.5:0.05), and ultrasonically dispersed for 30 min to obtain uniform catalyst ink. Each ink was then drop-coated onto a surface with an area of ​​2 × 2 cm². 2 The carbon paper electrode surface was naturally dried and used as the working electrode. The catalyst loading of each electrode was controlled at 5 mg / cm³. 2Using a platinum sheet as the counter electrode, the electrolyte was placed in an O2-saturated 0.05 M Na2SO4 electrolyte, and electrolysis was performed using a constant current of 10 mA applied to the working electrode in constant current mode. During electrolysis, 20 μL of electrolyte was added to a solution containing 20 μL of DMPO (0.22 mol / L). -1 The sample was mixed thoroughly in a centrifuge tube, then quickly transferred to a capillary tube and placed in a quartz EPR sample tube. It was then transferred to the resonant cavity of the EPR spectrometer, and EPR spectra were acquired at room temperature. The EPR test parameters were the same as before: resonance frequency 9.834 GHz. RS485 serial communication was used to coordinate the acquisition of the electrochemical sequence and the two-dimensional time series of the EPR.

[0049] The results are as follows Figure 6 As shown, the characteristic quartet signal of DMPO-·OH was detected in all three systems: 0.5 wt% SA-CuN4 / NC, 1.5 wt% SA-CuN4 / NC, and 2.7 wt% SA-CuN4 / NC, indicating that all three systems possess the ability to catalyze the formation of ·OH from O2. Comparing the characteristic peak intensities of the three systems, it can be seen that the EPR signal intensity of ·OH increases with the increase of copper content in the catalyst from 0.5 wt% to 1.5 wt% and then to 2.7 wt%, indicating that the amount of ·OH produced increases accordingly with the increase of the number of copper active sites. This result shows that in the SA-CuN4 / NC system, the formation efficiency of ·OH is positively correlated with the number of Cu active sites, further confirming that the CuN4 coordination structure is the key active center for catalyzing the selective three-electron reduction of O2 to ·OH.

[0050] Application Example 2: This application example reveals the dynamic self-reconfiguration behavior of SA-CuN4 / NC under electrochemical operating conditions using in-situ XAS technology.

[0051] In a three-electrode flow cell, using the SA-CuN4 / NC obtained in Example 1 as the working electrode, in-situ Cu K-edge XANES and EXAFS spectra were acquired in 0.05 M Na2SO4 solution at different cathode potentials (OCP, 0.8, 0.6, 0.4, 0.2 V vs. RHE). The results are as follows: Figure 7 As shown, as the potential decreases from 0.8 V to 0.2 V, the oxidation state of Cu gradually decreases. Simultaneously, a new Cu-Cu scattering peak appears at ~2.3 Å in the EXAFS spectrum, and its coordination number increases from 0.3 to 1.7, indicating that single-atom Cu sites aggregate under the cathode potential, forming Cu2-CuN2 (Cu3) clusters. When a positive potential (1.8 V) is applied or the potential is removed, the Cu-Cu peak disappears, and the structure reverts to the initial CuN4 state, proving that the reconstruction process is reversible.

[0052] Application Example 3: This application example evaluates the concentration of ·OH generated in the SA-CuN4 / NC system at different cathode potentials and its inactivation efficiency on ARB (E. coli HT115).

[0053] In the two-electrode system, using the SA-CuN4 / NC obtained in Example 1 as the cathode and a platinum sheet as the anode, in a solution containing 10 8 In a 0.05 M Na₂SO₄ solution containing CFU / mL E. coli HT115, constant potentials of 0.8, 0.6, 0.4, 0.2, and -0.1 V vs. RHE were applied, and the reaction was allowed to proceed for 1 minute. The results are as follows: Figure 8 As shown, as the cathode potential decreased from 0.8 V to 0.4 V, the single-atom Cu sites gradually underwent self-reconstruction, the ·OH generation concentration gradually increased, and the bacterial inactivation efficiency increased from 71.3% to 100% (8-log removal). These results indicate that by adjusting the cathode potential, the degree of self-reconstruction of single-atom Cu sites and their corresponding active structures can be precisely controlled, thereby optimizing the ·OH generation concentration. There exists an optimal potential (0.4 V in this system) at which single-atom Cu sites reconstruct into Cu2-CuN2 cluster active structures, resulting in optimal ·OH generation performance and thus achieving the best disinfection effect.

[0054] Application Example 4: The 1.5wt% SA-CuN4 / NC from Example 1, the 1.5wt% CuN3 / NC from Comparative Example 1, and the 2.7wt% SA-CuN4 / NC from Comparative Example 2 were used as electrochemical cathode materials in electrocatalytic disinfection reaction systems to evaluate the ability of these cathode materials to inactivate antibiotic-resistant bacteria (ARBs) and remove antibiotic resistance genes (ARGs) in situ on the surface. Escherichia coli (E. coli HT115) carrying the tetracycline resistance gene (tetB) was selected as a representative antibiotic-resistant bacterium.

[0055] It is used as the cathode in the electrocatalytic reaction system, where the anode is a platinum sheet electrode with an electrode area of ​​4 cm². 2 A two-electrode potentiostat was used as the DC power source, and a stable current of 10 mA was applied. The solution contained E. coli HT115 (40 mL, 10 mL). 8 Electrochemical disinfection was carried out in a 0.05 M Na2SO4 solution (CFU / mL) for 30 min at a temperature of 25°C and a pH of 7.

[0056] The results are as follows Figure 8 and Figure 9As shown in the figure, the 1.5wt% SA-CuN4 / NC system produced a moderate concentration of ·OH (~11.5 μM), achieving 100% inactivation of ARBs (8-log removal) within 1 min, and reducing the removal rates of intracellular ARGs (iARGs) and extracellular ARGs (eARGs) below the detection limit within 30 min. The 1.5wt% CuN3 / NC system in Comparative Example 1 primarily generated H2O2 via the two-electron oxygen reduction pathway, producing almost no ·OH, resulting in negligible inactivation of ARBs and minimal removal of ARGs. In contrast, the 2.7wt% SA-CuN4 / NC system produced an excessively high concentration of ·OH (~47.9 μM). While this rapidly disrupted the cell membrane, leading to the release of intracellular substances, the high concentration of ·OH induced significant bacterial aggregation. The resulting aggregates hindered further penetration and diffusion of ·OH into the bacterial cell, leading to... The ARB inactivation rate within 1 minute was only 44.4%, and the removal rate of eARGs was significantly lower than that of the 1.5 wt% CuN4 / NC system. These results indicate that the SA-CuN4 / NC cathode system can achieve precise control of the ·OH generation concentration by adjusting the metal loading. A moderate concentration of ·OH is key to achieving ultra-fast ARB inactivation and complete ARG removal, while excessive ·OH-induced bacterial aggregation significantly weakens the disinfection effect.

[0057] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A single-atom copper catalyst, characterized in that, The single-atom copper catalyst uses montmorillonite as a support, and C3N4 containing a CuN4 coordination structure is loaded on the surface of the support.

2. The single-atom copper catalyst according to claim 1, characterized in that, The loading of single-atom copper is 0.5-2.7 wt%.

3. A method for preparing a single-atom copper catalyst as described in claim 1 or 2, characterized in that, Includes the following steps: Montmorillonite was added to the copper source solution, and the first ultrasonic treatment was performed to remove Cu. 2+ Ion exchange enters the interlayer of montmorillonite, resulting in a mixture; Melamine was added to the resulting mixture, and the mixture was subjected to a second ultrasonic treatment to ensure homogeneity. The mixture was then pyrolyzed under an inert atmosphere to obtain the precursor. The obtained precursor was impregnated in an acid solution, washed and dried to obtain the SA-CuN4 / NC electrode material, namely the single-atom copper catalyst.

4. The preparation method according to claim 3, characterized in that, The copper source is selected from one or more of copper nitrate, copper chloride, and copper sulfate.

5. The preparation method according to claim 3, characterized in that, The mass ratio of the copper source, montmorillonite, and melamine is (0.239-1.912):2:2; The duration of the first or second ultrasound treatment is 20-40 minutes.

6. The preparation method according to claim 3, characterized in that, The inert gas in the inert atmosphere is selected from nitrogen and / or argon; The pyrolysis temperature is 500-600℃, and the pyrolysis time is 3-4 h; The immersion treatment time is 6-8 hours; the acid solution is 2-5 M H2SO4.

7. A cathode oxygen reduction reaction, characterized in that, Includes a cathode, said cathode comprising the single-atom copper catalyst of claim 1 or 2.

8. The application of the cathode oxygen reduction reaction according to claim 7 in in situ inactivation of antibiotic-resistant bacteria and removal of antibiotic resistance genes.

9. The application of the cathode oxygen reduction reaction as described in claim 7 in the efficient disinfection of activated O2.

10. The application according to claim 9, characterized in that, The specific method of the application is as follows: Using a two-electrode or three-electrode system, the single-atom copper catalyst is used as the cathode and a platinum sheet is used as the anode. Electrolysis is carried out in an aqueous solution containing a supporting electrolyte through a constant current or constant potential mode. The hydroxyl radicals generated in situ at the cathode are used to disinfect the target water body.